Systematic Risk and Accounting Determinants: An Empirical Assessment in the Indian Stock Market - Parthasarathy, Srikanth (Organizations and Markets in Emerging Economies, 2019)
This study explores the contemporaneous association between market determined risk measures and accounting determined risk measures using the large liquid non-financial stocks in the Indian stock market in the recent 2012-2017 period. Two measures of systematic risk and seven accounting determined risk measures are chosen based on prior research. This study uses three regression techniques, namely Ordinary Least Squares (OLS), stepwise regression and robust regression, to identify the influential accounting variables for the systematic risk measured by market beta. The results evidence that there is a high degree of contemporaneous association between market determined and accounting determined risk measures, with nearly 30% of the cross sectional variance in systematic risk explained by accounting determined risk measures. The results suggest that the accounting variables can be used in the predictive models of future risk, leading to superior decision making at the level of individual decision maker.